Influence of structure water on crystal structure of hydrated molybdenum oxide and its interesting photothermal catalytic performances under indoor ambient conditions. (December 2019) - Yang, Z.; Teng, F.; Gu, W.; Hao, W.; Shi, S.; Zhao, F.
Abstract: From the viewpoint of engineering application, it is highly desirable to develop a low-cost, fossil energy–saving degradation technology. In this work, hydrated molybdenum oxide (MoO3 ·0.55H2 O) is prepared by a simple chemical method. It is interesting that under indoor natural ambient conditions, 79% of methylene blue is degraded by hydrated molybdenum oxide after 150 min, but under the same conditions, anhydrous molybdenum oxide does not have any degradation activity. It is found that the outstanding ambient activity of hydrated molybdenum oxide is mainly attributed to the photothermal synergistic effect caused by structure water. On one hand, the coordination of structure water with molybdenum brings about the Jahn–Teller distortion of MoO6 octahedron, giving rise to Lewis acid sites that promote the adsorption and activation of oxygen. O2 –temperature-programmed desorption and H2 –temperature-programmed reduction profiles show that compared with MoO3, MoO3 ·0.55H2 O has a higher oxygen adsorption ability and a higher oxidation ability. Jahn–Teller effect is mainly responsible for the thermocatalytic activity. On the other hand, the ligand-to-metal charge transfer (LMCT) transfer from structure water to molybdenum obviously increases the light absorption, thus LMCT is mainly responsible for the photocatalytic activity The most important is that compared with conventional photocatalysis, no artificial light source equipment is required; compared with thermocatalysis, no extra heating equipment is needed. Thus, this mild degradation process is low-cost, energy-saving and space-saving, which is very promising for indoor or limited space cleaning. Graphical abstract: MoO3 ·0.55H2 O nanorods show an outstanding degradation activity under indoor natural weak light irradiation because of a photothermal synergistic effect caused by structure water. This mild degradation process is low-cost, energy-saving and space-saving. Image 1 Highlights: MoO3 ·0.55H2 O shows an outstanding weak light degradation activity for dye, due to a photothermal synergistic effect. Jahn–Teller distortion of MoO6 caused by structure water is responsible for thermocatalytic degradation. A ligand-to-metal charge transfer from H2 O to Mo is responsible for the photocatalytic degradation. This process is low-cost, energy-saving and space-saving, which is promising for indoor clean in practices.